Thermal comfort of green roofs with Cissus verticillata (Vitaceae) in tropical rural dwellings - Beltrán-Melgarejo Abraham; Vargas-Mendoza Mónica de la C.; Pérez-Vázquez Arturo; García-Albarado J. Cruz (Revista Mexicana de Ciencias Agrícolas, 2018)
Green roofs have taken rise because of the several benefits they provide, including thermal mitigation of buildings, and improving thermal comfort (TC). Although it is a desirable technology in warm, tropical areas, is required to lighten its conventional design, in order to adapt it to the tropical rural dwellings. This research was conducted in Veracruz, Mexico, for evaluating the TC provided by a prototype green roof based on the use of pergolas and Creeper Cissus verticillata (Vitaceae). The temperature under the roof sheet of rural households with and without green roof was compared. The TC of the rooms was measured using subjective vote (SV), the average predicted vote (APV), and the proportion of people uncomfortable (PPU), obtained from a group of evaluators resident and another visitor, who also rated their degree acceptance of this technology. The average temperature in the room with green roof was up to 4.5 °C lower (p< 0.05) than in rooms without green roof. The SV, APV, and PPU were higher (p< 0.01, p< 0.01 and p< 0.0001, respectively) in rooms without green roof, indicating a lower TC therein. Acceptance of the visiting group was significantly higher than that of the resident (p< 0.0001). It is concluded that by using green roofs as proposed is reached greater TC in tropical rural homes.